Comprehensive assessment of the capacity of sand and sandstone from aquifer vadose zone for the removal of heavy metals and dissolved organics - Ghaleb, Hala (2023)
Due to the drastic effect of produced water on the environment and its large quantity produced by the oil and gas industry, produced water treatment is a significantly growing challenge that requires serious attention. Produced water can be used as unconventional source of water in arid regions for underground water aquifer recharging through soil aquifer treatment (SAT), however, this requires sophisticated studies to avoid the contamination of the underground water. The present study investigates the efficacy of sand and sandstone from aquifer vadose zone for removing heavy metals and dissolved organic that are common contaminants in oil produced water. The removal of performance of soil samples has been evaluated on the laboratory scale at neutral pH at room temperature using synthetic oil produced water which contains heavy metals (Ni and Zn) and dissolved organics (phenol). The various experimental parameters were monitored and results indicated the sandstone displayed the highest removal of 98%–99% for both heavy metals and 26% for phenol than sand. The experimental data were fitted using four isotherm models, the Langmuir adsorption isotherm, the Freundlich isotherm, the Temkin isotherm model and the D–R isotherm. The Langmuir adsorption isotherm fitted well in a monolayer adsorption conceptual model on sand and sandstone. Kinetic modelling and analysis indicated that both soil samples followed the pseudo-second- order kinetics for metal ions and phenol. The 2D-COS FTIR was applied to analyse the interaction mechanism between the contaminants and sand and sandstone particles. The asymmetric Si–O band in sand minerals plays the prime response in Ni and Zn removal mechanisms whereas the asymmetric CO2−3 band decides for the removal mechanisms in sandstone. In the case of phenol adsorption, the interaction between phenol and Si–O bond is the predominant mechanism. Overall, these results summarize that sand and sandstone are effective for heavy metals removal than dissolved organic compounds.